PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM MENGHADAPI DISRUPSI TEKNOLOGI PENDIDIKAN - Fahira Choirun Nisa'; Muhamad Syahrul Salasa; Farah Nisrina; Abdul Razaq An-Nabil (STKIP Pesisir Selatan, 2025)
On the other hand, Generation Z students are more familiar with technology and demand interactive and digitally relevant learning experiences. This paradoxical situation emphasizes that the primary challenge facing madrasas in facing technological disruption lies not only in devices, but also in leadership and change management. This study examines the role of madrasah principals in responding to disruptions caused by digital education technology. This qualitative study uses literature review to analyze related concepts and theories. The findings highlight the crucial role of madrasah leadership in facing educational technology disruption through five main dimensions: leadership vision, digital transformation, learning technology integration, stakeholder collaboration, and dynamic technology adaptation. However, challenges such as limited funds, resistance to change, gaps in teachers' digital competencies, and the need to maintain a balance between modernization and religious values pose obstacles. This study concludes that visionary, adaptive, and transformative leadership is essential for the success of madrasahs. Therefore, it is recommended to strengthen leadership capacity, government policy support, and the development of a digital ecosystem that is in line with the identity of madrasahs.